Increasing Global Access to Education with Digital Technology - Huzaiman Hushin (International Journal of Education and Digital Learning (IJEDL), 2025)
Digital technology has significantly transformed the educational landscape, increasing access to education worldwide. With the rapid growth of the internet, mobile devices, and online platforms, education is no longer confined to traditional classrooms. This article explores how digital technology has opened new avenues for learning, especially for underserved populations and regions with limited educational infrastructure. By focusing on online learning platforms, Massive Open Online Courses (MOOCs), and mobile learning applications, the article examines how digital tools are democratizing education and bridging the global education gap. Additionally, the paper discusses the challenges and barriers that still exist, including digital divides, lack of infrastructure, and teacher preparedness, while also highlighting successful initiatives and case studies that have increased educational access. By leveraging the power of digital technology, education can become more inclusive, flexible, and equitable, ensuring that people from all backgrounds have the opportunity to learn and grow. The article concludes with recommendations for policymakers and educators to enhance the global impact of digital education.